Oxford HEXameter: laboratory high energy X-ray diffractometer for bulk residual stress analysis - Korsunsky, A; Zhang, S; Dini, D; Vorster, W; Liu, J (Trans Tech Publications, 2006)
Diffraction of penetrating radiation such as neutrons or high energy X-rays provides a powerful non-destructive method for the evaluation of residual stresses in engineering components. In particular, strain scanning using synchrotron energy-dispersive X-ray diffraction has been shown to offer a fast and highly spatially resolving measurement technique. Synchrotron beamlines provide best available instruments in terms of flux and low beam divergence, and hence spatial and measurement resolution and data collection rate. However, despite the rapidly growing number of facilities becoming available in Europe and across the world, access to synchrotron beamlines for routine industrial and research use remains regulated, comparatively slow and expensive. A laboratory high energy X-ray diffractometer for bulk residual strain evaluation (HEXameter) has been developed and built at Oxford University. It uses a twin-detector setup first proposed by one of the authors in the energy dispersive X-ray diffraction mode and allows simultaneous determination of macroscopic and microscopic strains in two mutually orthogonal directions that lie approximately within the plane normal to the incident beam. A careful procedure for detector response calibration is used in order to facilitate accurate determination of lattice parameters by pattern refinement. The results of HEXameter measurements are compared with synchrotron X-ray data for several samples e.g. made from a titanium alloy and a particulate composite with synchrotron measurements and strain resolution close to 2x10⁻⁴ is routinely achieved by the new instrument.